Loading presentation...

Present Remotely

Send the link below via email or IM

Copy

Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

DeleteCancel

Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.
You can change this under Settings & Account at any time.

No, thanks

Solving slope intercept, point-slope, and standard form

No description
by

ashley coates

on 27 May 2011

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of Solving slope intercept, point-slope, and standard form

Step 1:
solving point slope equations. First you start out with
point-slope form:
y-y1=m(x-x1) Part one: point-slope form next you have your ordered pairs such as
(3,2) and (1,4) next you find your m, or slope by using the equation
y2-y1
x2-x1 now, pick an ordered pair and use that and your slope to plug them into the equation y-y1=m(x-x1) using the ordered pair (3,2) and the slope -1

y-2=-1(x-3)

and that's point-slope form. so your equation will be
4-2
1-3 4-2 =2
1-3 =-2 this is simplifies to -1 Lets try a problem:
coordinate points: (3,10) and (2,5) answer:
y-10=5(x-3) Explanation:
5-10
2-3
this equals 5 (your slope)

next, plug the coordinate point of your choice and the slope into the equation lets try a couple more: 1. (2,7),(4,1) 2. (3,8),(4,6) 3. (10,7),(6,3) Part two: standard form step one: solving standard form equations first, you take two coordinate points and put them in point-slope form. standard form is the equation
Ax+By=C (3,1) (4,2)

2-1
4-3
which simplifies to 1
y-2=1(x-4)
this is NOT your answer
only a step into getting your answer next you simplify the equation,like this:
y-2=1(x-4)
*distribute the one to the x and the four
1(x)-1(-4)
y-2=1x-4
*next subtract 1x from each side
y-2 = 1x-4
-1x -1x
-1x-1y-2=-4
+2 +2
*now you add 2 to each side which is called the inverse operation because it is the opposite.
your answer should be:
-1x-1y=-4 1-7
4-2
=-4
y-1=-4(x-4)
-or-
y-7=-4(x-2) 6-8
4-3
=-2
y-8=-2(x-3)
-or-
y-6=-2(x-6) 3-7
6-10
=1
y-7=1(x-10)
-or-
y-3=1(x-6) now that you know how to write an equation in standard form,why dont you try a couple on your own put the equations into standard form:
1.)y-6=2(x-4) 2.)y-3=1/2(x-8) 3.)y+3=2(x-1) 1.) y-6=2x-8
-2x -2x
-2x-1y-6=-8
+6 +6
-2x-1y=-2 2.)y-3=1/2x-4
-1/2x -1/2x
-1/2x-y-3=-4
+3 +3
-1/2x-y=-1 3.)y+3=2(x-1)
y+3=2x-2
-2x -2x
-2x+y+3=-2
-3 -3
-2x+1y=-5 i hope this was easy to understand and helped.
Full transcript